Rhetoric, hermeneutics, and translation in the Middle Ages: academic traditions and vernacular texts - Copeland, Rita (Cambridge studies in medieval literature, 1991)
Translation played a crucial role in the emergence of vernacular literary culture in the Middle Ages. This is the first book to consider the rise of translation as part of a broader history of critical discourses from classical Rome to the late Middle Ages, and as such adds significantly to our understanding of the development of European culture